Exploring pro-environmental tourism practices shaping Arctic holiday experiences : insights of tourism experts from Finnish Lapland - Kainulainen, Emmi (fi=Lapin yliopisto|en=University of Lapland|, 2024)
Climate change brings challenges for tourism industry, and specifically in the Arctic region which is warming faster than any other part of the world. At the same time, Arctic has gained public interested, resulted in drastic tourism growth, which in hand conflicts with the climate change. For which reason, this study focused on concerns over the future of Arctic region in the era of climate change and rapid tourism growth, and for that reason explored from the perspective of tourism experts, what tourism has to offer for the Arctic, where tourists would work as active contributors. The framework of the study was based on practice theory, in order to understand, how with the help of practices, tourists could be involved. The study was qualitative in nature, and the theoretical paradigm of the research was based on social constructionism to investigate the multiple realities from an insider’s perspective, in this case the insiders were tourism experts from Finnish Lapland, consisting of five interviews. The findings indicated three key practices: Nudging practices, nature-oriented pro-environmental practices and co-creation practices, which together create a concept of pro-environmental practices. In addition, several challenges and opportunities emerged from the findings regarding the implementation of the practices.